Evaluación del uso del propóleo, (2g,3g), como suplemento en la alimentación de las vacónas de 1 a 2 años de edad en el centro experimental académica salache (CEASA). - Córdova Torres, Jennifer Estefanía (2021)
The investigation was carried out at the Technical University of Cotopaxi at the Salache Academic Experimental Center (CEASA), which is located in the Salache parish, Salache sector, in the investigation 9 bovines between 1 to 2 years of age typical of the institution were handled of the Holstein breed, with an average weight of 312.66 Kg, in order to obtain thanks to bees called propolis, it has several properties, main resins and vegetable balsams ( 50%) ; waxes(30%); essential oils (10%) and pollen. (YK, 2013). In this research, different treatments were applied having three animals for control (they did not receive propolis), three for treatment1 (2 grams of propolis), and 3 animals for the treatment 2 (3 grams of propolis), it was administered orally, The project lastad two months for the researche, a forage sample (alfalfa, ray grass, clover, kikuyo) was taken from the pastures and also a propolis sample that was collected from the beekeeping project, to be analyzed throungh a bromatological examination The properties were taken into account (humidity 3.18%, ashes 8.10%; E.E41.17%; PROTEIN 1.18%; fiber 9.39%; E.L.N 39.56%), in the cows blood test were carried ou, to obtain initial, intermediate and end data of immunoglobulin A, in addition, a weekly weight was taken, giving the results of the control weight (propolis was not administered), the initial average weight was 312 Kg and the final weight 321.66 Kg; treatment 1 with administration of propolis(2gr), initial average weight 322.33 Kg and end weight 336 Kg; in tretment 2, the average initial weight was 303.66 Kg and the end weight was 318.66 Kg. in the immunoglobulin A tests, the result treatment g/L, had an average (0.16 g/L), in the end exam an average in immunoglobulins A, in treatments1, (0.17 g/L), at the end of the tube an average of (0.24 g/L), in treatment 2, it had an average (0.12 g/ L), at the end (0.32 g/ L).